Duration and Persistence in Multidimensional Deprivation: Methodology and Australian Application - Dahlquist, C; Repp, A; Munk, D; Laarhoven, T; Johnson, J (My University, 2003)
The present study investigated applications of the disequilibrium model of reinforcement in typical classroom contexts with students perceived by their teachers as being difficult to motivate. The disequilibrium model states that reinforcing effects are produced when access to any response (task) is constrained so that an individual cannot meet an (unconstrained) baseline level for that response (task). The implication of the model is that low-probability (low-preference) responses can be constrained and used as reinforcers, a seeming contradiction to the common practice of using a high-probability response to reinforce increases in a low-probability response. The present study investigated the effects of disequilibrium schedules of reinforcement with six students with several disabilities in classroom contexts. The specific research questions were (i) whether disequilibrium schedules would produce reinforcing effects if both the instrumental and contingent tasks were of moderate to low preference for the student; (ii) how effects of disequilibrium schedules would compare with those of a teacher-generated contingency; and (iii) what effects disequilibrium schedules would have with students who engage in non-task responding during the baseline period. Results suggest that disequilibrium schedules are effective when used with moderate to low-preference tasks. Results of the comparison with teacher-generated contingencies were mixed. Results do suggest that the presence of higher levels of non-task responding during the baseline period may affect subsequent effectiveness of disequilibrium schedules calculated from the baseline.
Keywords: Children -- School age; Childhood and child development; Children; School age; Childhood and child development